An Integrated Arterial Remodeling Hydrogel for Preventing Restenosis After Angioplasty - Chenxing Fu; Qiu Li; Minghui Li; Jiexin Zhang; Feiran Zhou; Zechuan Li; Dongyue He; Xinyi Hu; Xiaodong Ning; Wenjie Guo; Weirun Li; Jing Ma; et al. (Advanced Science, 2024)
Abstract The high incidence of restenosis after angioplasty has been the leading reason for the recurrence of coronary heart disease, substantially increasing the mortality risk for patients. However, current anti‐stenosis drug‐eluting stents face challenges due to their limited functions and long‐term safety concerns, significantly compromising their therapeutic effect. Herein, a stent‐free anti‐stenosis drug coating (denoted as Cur‐NO‐Gel) based on a peptide hydrogel is proposed. This hydrogel is formed by assembling a nitric oxide (NO) donor‐peptide conjugate as a hydrogelator and encapsulating curcumin (Cur) during the assembly process. Cur‐NO‐Gel has the capability to release NO upon β‐galactosidase stimulation and gradually release Cur through hydrogel hydrolysis. The in vitro experiments confirmed that Cur‐NO‐Gel protects vascular endothelial cells against oxidative stress injury, inhibits cellular activation of vascular smooth muscle cells, and suppresses adventitial fibroblasts. Moreover, periadventitial administration of Cur‐NO‐Gel in the angioplasty model demonstrate its ability to inhibit vascular stenosis by promoting reendothelialization, suppressing neointima hyperplasia, and preventing constrictive remodeling. Therefore, the study provides proof of concept for designing a new generation of clinical drugs in angioplasty.